2002
DOI: 10.1149/1.1456535
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure and First Cycle Redox Mechanism of Layered Li[sub 1.2]Cr[sub 0.4]Mn[sub 0.4]O[sub 2] Cathode Material

Abstract: Electrochemical, X-ray diffraction, and K and L edge X-ray absorption data are reported for the layered cathode material Li 1.2 Mn 0.4 Cr 0.4 O 2 . The structural data show that this material can be understood as a solid solution of the layered phases Li 2 MnO 3 and LiCrO 2 , comprising tretravalent Mn and trivalent Cr, with approximately 0.2 lithium incorporated in the transition metal layers. According to the analysis of the K edge extended X-ray absorption fine structure, lithium ions in the transition meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
132
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 10 publications
12
132
0
2
Order By: Relevance
“…It has been reported that with increasing c/a ratio beyond 4.90, the ordering of the layered structure increases and the crystal structure becomes more hexagonal. 15,16 In this study, the c/a values of all the samples were is an effective indicator of the disorder of the cations in the lattice, with higher ratios representing lower degrees of cation mixing. This intensity ratio linearly increased with increasing calcination temperature, implying that increased calcination temperatures facilitated better layering of the structures and reduced cation mixing.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…It has been reported that with increasing c/a ratio beyond 4.90, the ordering of the layered structure increases and the crystal structure becomes more hexagonal. 15,16 In this study, the c/a values of all the samples were is an effective indicator of the disorder of the cations in the lattice, with higher ratios representing lower degrees of cation mixing. This intensity ratio linearly increased with increasing calcination temperature, implying that increased calcination temperatures facilitated better layering of the structures and reduced cation mixing.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, X-ray absorption near edge structure (XANES) analyses were carried out to compare changes of local structure around the Mn, Fe, and Ni atoms in Li 1.2 (Fe 0. 16 Mn 0.32 Ni 0.32 )O 2 samples. Figure 4 shows the Mn, Fe and Ni K-edge XANES spectra of Li 1.2 -(Fe 0.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that with increasing c/a ratio beyond 4.90, the ordering of the layered structure increases and the crystal structure becomes more hexagonal. 4 However, it is well known that the c/a value and cation mixing amount showed change with increase in Ni content. The higher Ni content resulted in worse hexagonal ordering along with a higher cation mixing.…”
Section: -15mentioning
confidence: 99%
“…[2][3][4] The olivine type LiFePO 4 is a promising cathode material for LIB due to its low cost and stable cyclic performance. But, low electronic conductivity and low cell voltage (~3 V) of LiFePO 4 confined its possibility to utilize in HEVs.…”
mentioning
confidence: 99%